Interaction of AURKA with TRIM28 revives dormant LSCC cells via Akt signaling pathway to promote LSCC metastasis - Liyun Yang; Liang Geng; Xinxin Zhang; Jing Lu; Hao Zhang; Geping Wu; Shuixian Huang (Cancer Cell International)
Abstract Background Specific molecular mechanisms by which AURKA promoted LSCC metastasis were still unknown. Methods Bioinformatic analysis was performed the relationship between TRIM28 and LSCC. Immunohistochemistry, Co-IP assay, Rt-PCR and Western Blot were used to examine the expression of related molecular. Flow cytometry was used to examine cell numbers of G0/G1 phase. Plate colony formation, wound healing, migration, invasion and tail vein injection in nude mice assays were applied to examine the proliferation, movement, migration, invasion and metastasis of LSCC. Results TRIM28 was significantly correlated with LSCC. TRIM28 highly expressed in LSCC and the high TRIM28 expression was related to TNM stage and poor clinical prognosis. Furthermore, AURKA could regulate TRIM28. In addition, deprivation TRIM28 expression induced LSCC cells into dormant state and inhibited LSCC metastasis. Akt signaling pathway played an essential role in promoting the tumor-promoting effects induced by TRIM28. Conclusion AURKA mediated TRIM28 to revive dormant LSCC cells via Akt signaling pathway to promote LSCC metastasis, targeting TRIM28 might provide a potential treatment strategy for LSCC.